Eva contro Eva. Identità femminile ed ebraica nell’opera di Rose Ausländer (Altre Modernità, 2014)
As the first woman in the religious traditions of Judaism, Christianity, and Islam, Eve comes to symbolize all women. In the Western civilization, her creation has been viewed as secondary to the man’s; her substance, derivative; her eating the fruit of the forbidden tree, culpable; her status relative to her man, subordinate. Rose Ausländer's poetry emphasizes Eve's active role in the Garden of Eden and constitutes a playful revision of the Biblical creation myth. In this manner, she continues the project of midrash; she mines the biblical texts to yield new treasures buried within them.